What Is and How to Improve the Local History Material in History Learning - Winarti, Murdiyah (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2012)
The simple formula used to explain the local history in this paper is the history that tells about the dynamis life of a community with its culture in an area, a certain regionality. In the â€œlocalityâ€ perspective of location or geography aspect which include the village, city, region, and province and its variety, Indonesia would have many of it. However, the local history has a strategic role while providing a wide possibility in improving the national history writing. In term of theme, the posibility for the local hidtory materials writing and develoment is interesting and open. However, there is a challenge, which is the limitation in gaining the historical resources, particularly the written one. Therefore, the local history material development in Indonesia relies on the oral tradition and oral history.